Religio- political position of China in Xinjiang (70-80 years). - Smagulova., K. K. (Journal of Oriental Studies, 2016)
This article is devoted to ethnical problems of Xinjiang minority, socio- political situation, the freedom of confession and its place in policy, processes of integration. The place of the main Xinjiang religion- Islam, traditions and customs of Muslim folks in Chinese society are also described. In this way articleconsiders the processes of development features of religious identities and confessional relations in Xinjiang.